New Technique of Filtration Rate Measurement In Flow Through System With Constant Concentration of Algae - Djoko Suprapto (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2002)
Sebuah tekhnik baru pengukuran tingkat filtrasi bivalvia telah dirancang dan digunakan untuk mengukur filtrasi dari Pecten maximus L. Prinsip penghitungan teknik pengukuran filtrasi ini adalah menghitung penurunan konsentrasi fitoplankton dalam media pengukuran. Alat ini selanjutnya diuji untuk menghitung konsumsi fitoplankton delam hubungannya dengan berat kering P. maximus L. Hasil pengukuran dinyatakan dalam persamaan alometrik (Y=aXb). Konsumsi fitoplankton untuk populasi Brest, Saint Breiux. Scotlandia dan lrlandia berturut-turut adalah sebagai berikut: 85,17X012, 97,18X0,16, 85,98X0,18 dan 75,70X0,18 Kata kunci: laju filtrasi, scallop, berat kering A flow through system for measuring filtration rate of bivalve is described. The principle of measurement was to calculate the decrease of algal concentration in the water medium where the experimental animal was placed. The measuring system was tested to calculate the phytoplankton consumption related to dry body weight of scallop Pecten maximus L. coming from different populations. This corretetion is expressed by allometric equation (Y=aXb). Allometric equation of Brest, Saint Brieux. Scotland, Ireland populations are: 85,17X012, 97,18X0,16, 85,98X0,18 dan 75,70X0,18 successivelyKeywords: filtration rate, Scallop, dry body weight